PENGARUH KREATIVITAS IKLAN, DAYA TARIK PRODUK, DAN CUSTOMER SATISFICATION TERHADAP LOYALITAS KONSUMEN PROVIDER INDOSAT OOREDOO DI KOTA BATAM: PENGARUH KREATIVITAS IKLAN, DAYA TARIK PRODUK, DAN CUSTOMER SATISFICATION TERHADAP LOYALITAS KONSUMEN PROVIDER INDOSAT OOREDOO DI KOTA BATAM - HALAWA, AYU DESI PITTAULI (SCIENTIA JOURNAL, 2025)
The development of providers in Indonesia is expected to advance further along with the rapid digital transformation. In improving customer service experience, several providers in Indonesia have developed quite a variety of supporting features to increase consumer loyalty. Indosat Ooredo is one of the telecommunications service providers in Indonesia. Several methods that have been implemented to developing customer loyalty include aspects of advertising creativity, the attractiveness of the products offered, and customer satisfaction. This quantitative descriptive study was conducted with the aim of determining the effect of the variables of advertising creativity (X1), attractiveness (X2), and customer satisfaction (X3) on the loyalty of Indosat Ooredo users in Batam City. The data collection method used was a questionnaire with 380 respondence. The results of the study showed that advertising creativity (X1), attractiveness (X2), and customer satisfaction (X3) had a significant influence on the loyalty of Indosat Ooredoo users. This is because satisfied customers tend to feel more attached to the brand and have positive experiences that encourage them to continue using the product or service.